Seroepidemiological investigation of Getah virus in the China-Myanmar border area from 2022-2023 - Liu, Hao; Hu, Jin; Li, Li-Xia; Lu, Zi-Shuo; Sun, Xiu-Tao; Lu, Hui-Jun; Jin, Ning-Yi; Zhang, Lei; Zhang, Li-Na (Frontiers in Microbiology, 2023)
Getah Virus (GETV) is an RNA virus that is transmitted by mosquitoes and can cause disease or death in a variety of vertebrates. Its prevalence is increasingly severe in Asia. This study conducted a GETV epidemiological investigation on 1,300 bovine sera collected in the Honghe Prefecture of Yunnan Province on the China-Myanmar border from 2022 to 2023. The positive rate of GETV antibodies in bovine serum in Honghe Prefecture was determined to be 20.25% through indirect ELISA methods.Using Real-time PCR methods to detect GETV RNA in bovine serum, the positive rate was 0.23% (3/1300), and viral nucleic acids were only detected in three bovine sera in Jianshui area in 2022. The YN2305 strain was successfully isolated from mouse neuroblastoma (N2a) cells and the complete gene sequence was obtained. All the above results indicate the existence of GETV infection in cattle in Honghe Prefecture, Yunnan Province. Homology and genetic evolution analysis found that the isolated strain has a high homology with the JL1808 strain isolated from cattle in 2018, with a nucleotide identity of 100%, and a nucleotide identity of 99.8% with the SD17-09 strain isolated from foxes in 2017. Compared with the nucleotides of 44 virus strains published in Genbank, YN2305 has multiple nucleotide site mutations in the structural gene E2 and non-structural gene NS.The nucleotide and amino acid identity of the E2 gene are 94.2-100% and 96.4-100%, respectively. Genetic evolution analysis found that this virus strain is most closely related to the bovine origin This is a provisional file, not the final typeset article JL1808, and it is in gene group III with HuN1, Kochi-01, SD17-09, MI-110-C1, MI-110-C2 strains that causes significant clinical symptoms in Chinese pig, fox and horse populations, belonging to the same evolutionary branch. This study determined the infection rate, genotype, and main prevalence areas of GETV in bovine sera in the China-Myanmar border area. Therefore, the epidemiological investigation of GETV infection in multiple animal hosts should be further expanded, and research on its pathogenicity and vectors should be carried out.